Hand, foot and mouth disease and herpangina caused by enterovirus A71 infections: a review of enterovirus A71 molecular epidemiology, pathogenesis, and current vaccine development - Yu-Kang Chang; Kou-Huang Chen; Kow-Tong Chen (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
ABSTRACT Enterovirus A71 (EV-A71) infections are one of the main etiological agents of hand, foot and mouth disease (HFMD) and herpangina worldwide. EV-A71 infection is a life-threatening communicable disease and there is an urgent global need for the development of vaccines for its prevention and control. The morbidity rate of EV-A71 infection differs between countries. The pathogen’s genetic lineages are undergoing rapid evolutionary changes. An association between the occurrence of EV-A71 infection and the circulation of different genetic strains of EV-A71 virus has been identified around the world. In this review, we present and discuss the molecular epidemiology and pathogenesis of the human disease caused by EV-A71 infection, as well as current prospects for the development of an EV-A71 vaccine.